Problems of social medicine in works Helena Radlińska – the pioneer of Polish social pedagogy - Filipczak, Katarzyna; Czernicki, Jan (European Journal of Clinical and Experimental Medicine, 2005)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The development of social pedagogy in Poland as an academic discipline is connected with the works of H. Radlińska – a pioneer of the discipline in Poland. The problems of healthcare were not strange to Ms Radlińska, her medical and nursing experience influenced her later work on empirical pedagogy and the theory of social work. She stressed the fact that the theory of social work comprises many disciplines to be used in nursing. A good example can be so called „education for the sake of health", which she regarded as a part of health awareness. Developing an active lifestyle of patient, treating then individually, making then work on their own were particularly important aspects of health awareness according to Ms Radlińska. She also stressed individual and group hygiene as well as heal the prevention.